O que o "que" sinaliza? Estudo das relações retóricas envolvendo a partícula "que" em textos jornalísticos - Oliveira, Ligianne Barbosa Rosa de (2024)
The “QUE” is a word in the Portuguese language that has different classifications and varied grammatical functions, and therefore establishes various semantic and coherence relationships, also known as rhetorical relationships. Thus, our objective in this research is to analyze the behavior of the linguistic element “QUE” in the rhetorical relationships identified in the CSTNews corpus, which consists of 50 clusters of news texts in Brazilian Portuguese. Our analysis is based on Rhetorical Structure Theory (RST), a descriptive theory that studies text organization by characterizing the relationships between parts of discourse (Matthiessen & Thompson, 1987). In this research, we identified and annotated the signaling elements that, along with “QUE”, contribute to the construction of these relationships. Fifty texts from the CSTNews corpus were annotated, consisting of news from various news sources, with the largest being from each cluster. We found a total of 2,514 annotated relationships. Out of these, 289 rhetorical relationships are established with the help of “QUE”. The “QUE” denotes the following rhetorical/coherence relationships: Attribution, Comparison, Condition, Contrast, Elaboration, Explanation, Interpretation, List, Non-volitional-result, Same-unit, Parenthetical, Purpose, Volitional cause, with predominance of Elaboration and Attribution relationships. In some examples of certain relationships, such as Elaboration, “QUE” appears alone; however, in most cases, there is another element accompanying it, constructing the rhetorical relationship, such as punctuation and verbs. This research offers various contributions to linguistic study, including aiding in the development of the RST annotation manual, as well as the POeTiSA project.